APPLICATION OF THE SAS METHOD USING SONG MEDIA IN IMPROVING THE BEGINNING READING ABILITY OF CLASS II STUDENTS OF STATE PRIMARY SCHOOL COT KUTA - Eli Yusnita; Siti Mayang Sari; Akmaluddin; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The research, entitled "Application of the SAS Method with Song Media inImproving Beginning Reading Ability of Class II Students of SDN Cot Kuta",aims to determine the activities of teachers and students in the application ofthe SAS method with Song Media as well as improving students' readingcomprehension skills through the application of the SAS method with songmedia. in class II SDN Cot Kuta. This study uses a qualitative approach andthe type of PTK research. Subjects in the study of class II students were 22.Data collection techniques were carried out using observation sheets and tests.Data analysis uses the frequency distribution formula. Based on the results ofthe study it can be seen that the teacher's activities in the process of managinglearning in cycle I by applying the SAS method and song media achieved apercentage value of 73.75% in the good category. In cycle II it increased to85.52% with a very good category. Student activities in the learning processin cycle I by applying the SAS method and song media achieved a percentagevalue of 70% in the good category. In cycle II it increased to 94.44% with avery good category. Students' initial reading ability in cycle I was 64%, incycle II it rose to 86%. So it can be concluded that improving students' initialreading skills through the SAS method and song media can improve theirinitial reading skills.